2019
DOI: 10.3390/molecules24091654
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, X-ray Analysis, Biological Evaluation and Molecular Docking Study of New Thiazoline Derivatives

Abstract: A series of new thiazoline derivatives were synthesized. Structure analyses were accomplished employing 1H-NMR, 13C-NMR, X-ray and MS techniques. The in vitro antitumor activities were assessed against human hepatocellular carcinoma (HepG-2) and colorectal carcinoma (HCT-116) cell lines. The results revealed that the thiazolines 5b and 2c exhibited significant activity against the two cell lines. The in vitro antimicrobial screening showed that the thiazolines 2c, 5b and 5d showed promising inhibition activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A review of the few available literature data on the anticancer properties of thiazolines suggests that they are potent inhibitors of PIM kinases, a type of serine/threonine kinase abnormally expressed in many cancers [19,20]. Other biological activities of thiadizole and functionalized thiazoline are reported in the literature as well [21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the few available literature data on the anticancer properties of thiazolines suggests that they are potent inhibitors of PIM kinases, a type of serine/threonine kinase abnormally expressed in many cancers [19,20]. Other biological activities of thiadizole and functionalized thiazoline are reported in the literature as well [21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Mabkhot et al 128 successfully synthesized a series of novel thiazoline compounds. The reaction sequence for the synthesis of thiazolines 221a–e involved treatment of dione 219a/b with 1° amines 220a–c at room temperature in ethanolic media.…”
Section: Reactivity and Application Of Thiazolinesmentioning
confidence: 99%
“…However, very few studies have focused on the synthesis of thiazole spirocyclic derivatives containing thiazole spirocycles. For example, Mahapatra et al and Mabkhot et al reported excellent methods for synthesizing thiazole spirocyclic backbone compounds, which are primarily formed through efficient spirocyclization reactions (Scheme a). Therefore, although constructing structurally novel spirothiazole spirocyclic backbone molecules using environmentally friendly methods is challenging, it holds considerable research value.…”
Section: Introductionmentioning
confidence: 99%